Analisis Perhitungan Retensi Optimal Reasuransi Stop Loss dengan Metode Value at Risk (VaR) - Oktavia, Grace; Addini, Fida Fathiyah; Prihandoko, Dedy Irawan (Universitas Cokroaminoto Palopo, 2024)
Insurance companies do not cover the entire risk of policyholders. The risk is generally transferred in part to the reinsurance company. Stop loss reinsurance is a form of reinsurance contract where there is a limit on the risk value that can be borne by the insurance company. This value is the retention value or retention limit in the reinsurance contract, which is the maximum risk or insurance value that can be borne by the insurance company. Determining the right retention value is very important. Optimizing the Value at Risk risk measure is one approach in calculating optimal retention. Optimal retention criteria were identified in this research so that optimal retention values ​​could be calculated. This research uses a large claim data sample with the Weibull distribution. Determining optimal retention depends on the distribution of claim sizes and loading factors (additional factors in the insurance policy). With a 95% confidence level, for loading factors of 10%, 15%, and 20%, the estimated optimal retention values ​​are 1,080.56, 1,393.54, and 1,567.20. This means that the risk transferred to the reinsurer is the remaining claim amount, if the claim size exceeds the optimal retention value.